Molecular and Cell Biology Methods for Fungi - Sharon, Amir.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2010)
With the development of fungal transformation systems and the deciphering of an increasing number of fungal genomes, this diverse clade of heterotrophic eukaryotic organisms has proven to be ideal for molecular work and highly serviceable as model systems to study basic processes with results that are applicable to many organisms, including humans. In Molecular and Cell Biology Methods for Fungi, experts in the field provide an up-to-date set of practical protocols covering a range of frequently used methods used to study molecular and cellular aspects of fungal biology. The included classical protocols such as transformation systems and traditional protein analysis methods, which have been widely used for many years, alongside the most advanced techniques such as genome amplification, whole genome knockout methods, and sophisticated in vivo imaging techniques will prove to be easily adaptable and useful in a wide range of species. Written in the highly successful Methods in Molecular Biology™ series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and notes on troubleshooting and avoiding known pitfalls. Comprehensive and up-to-date, Molecular and Cell Biology Methods for Fungi seeks to provide cutting-edge techniques in order to aid both experienced fungal research laboratories as well as those that are interested in using fungi as hosts to study their favorite genes.
Fungal Transformation and Gene Knockout -- Protoplast Transformation of Filamentous Fungi -- Electroporation and Agrobacterium-Mediated Spore Transformation -- High-Throughput Construction of Gene Deletion Cassettes for Generation of Neurospora crassa Knockout Strains -- Development of Impala-Based Transposon Systems for Gene Tagging in Filamentous Fungi -- DelsGate: A Robust and Rapid Method for Gene Deletion -- Gene Silencing for Functional Analysis: Assessing RNAi as a Tool for Manipulation of Gene Expression -- Detection and Quantification of Fungi -- Analysis of Fungal Gene Expression by Real Time Quantitative PCR -- Identification of Differentially Expressed Fungal Genes In Planta by Suppression Subtraction Hybridization -- Quantification of Fungal Infection of Leaves with Digital Images and Scion Image Software -- Expression Profiling of Fungal Genes During Arbuscular Mycorrhiza Symbiosis Establishment Using Direct Fluorescent In Situ RT-PCR -- Application of Laser Microdissection to Study Plant–Fungal Pathogen Interactions -- Multiplex Gene Expression Analysis by TRAC in Fungal Cultures -- Amplification of Fungal Genomes Using Multiple Displacement Amplification -- Microscopy and Protein Analysis -- Biochemical Methods Used to Study the Gene Expression and Protein Complexes in the Filamentous Fungus Neurospora crassa -- Measuring Protein Kinase and Sugar Kinase Activity in Plant Pathogenic Fusarium Species -- A Detailed Protocol for Chromatin Immunoprecipitation in the Yeast Saccharomyces cerevisiae -- A Method to Visualize the Actin and Microtubule Cytoskeleton by Indirect Immunofluorescence -- Fluorescence In Situ Hybridization for Molecular Cytogenetic Analysis in Filamentous Fungi -- Live-Cell Imaging of Microtubule Dynamics in Hyphae of Neurospora crassa -- Methods to Detect Apoptotic-Like Cell Death in Filamentous Fungi -- Evaluation of Antifungal Susceptibility Using Flow Cytometry -- Preparation of Fungi for Ultrastructural Investigations and Immunogoldlabelling -- Split-EGFP Screens for the Detection and Localisation of Protein–Protein Interactions in Living Yeast Cells.
Keywords: Cell biology; Biochemistry; Mycology; Microbiology; Cell Biology; Biochemistry, general; Mycology; Eukaryotic Microbiology